Viareggio, 29 luglio 2006 - Vari, Autori (Il sogno della farfalla, 2006)
A debate on the problem of justice and prisons was held in Viareggio on 19 July 2006. The participants included the psychiatrist Massimo Fagioli, the deputy Gennaro Migliore and the editorial director of “Left”, Luca Bonaccorsi. The debate followed the parliamentary decision to grant a pardon in order to improve the difficult prison conditions. Among other themes discussed was the need to go beyond the current political emergency and embark on a number of cultural considerations such as the concept of a penalty normally intended as a punishment and as such indicative of an negative view of human nature, or the distinction between delinquency and mental illness.